Error Analysis of Applying Inflectional Morpheme in Descriptive Writing at Tenth Grade in SMK Negeri 14 Samarinda - Pradana, Febrian Rizqi; Fauzan, Umar (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2021)
The background of this research were difference between word formation in Indonesian and English can cause some errors in students` writing. Errors are the result of incomplete learning and linguistic incompetency of the learners and errors cannot be self-corrected. Therefore, the errors made by students indicate that the learners do not mastered English yet. To know what are the errors made by the learner, it needs to use error analysis (EA). The objective of this research was to know the errors in applying inflectional morphemes made by students in descriptive writing. The research used descriptive qualitative. The main instrument is document. This research is carried out on the tenth grade students of SMK Negeri 14 Samarinda. There are 18 students as participants. The result showed that types of errors in the use of English inflectional morphemes that were found in this research only five types from eight types. They are plural inflection, possessive inflection, superlative inflection, past participle inflection, and third-person singular inflection. Which the rest of the types of errors (progressive inflection, past tense inflection, and comparative inflection) were not found. It also showed that plural inflection error was on the first rank with sixteen errors, then it was followed by third-person singular inflection error on the second rank with six errors, on the third rank were possessive inflection and past participle tense inflection with five errors, and the last was superlative inflection with four errors.